The Role of Artificial Intelligence in e-HRM, e-Marketing and Fintech Practices in the Medicine, Healthcare, and Life Sciences Sector of Bangladesh: Opportunities, Difficulties, Functions and Strategic Implications - Azmir Hossain, Md.; Datta, Sohag; Ferdousi, Bushra; Akhter, Nazma (Cuestiones de Fisioterapia, 2024)
Bangladesh’s healthcare and life sciences sector is undergoing a rapid digital shift under the Smart Bangladesh vision in 21st century. This article presents a practice‑oriented synthesis based on secondary data from 2022–2024 to examine how Artificial Intelligence (AI) is transforming three intertwined domains: electronic Human Resource Management (e-HRM), e‑Marketing, and Fintech. This study outlines opportunities (efficiency, personalization, inclusion), difficulties (data quality, bias, interoperability, regulatory gaps), core functions being deployed (predictive HR analytics, marketing automation, risk scoring for digital payments), and strategic implications for health system resilience, equity, and competitiveness. This paper concludes with an actionable roadmap for payers, providers, regulators, and innovators in Bangladesh.